Advances in control of agriculture and the environment. - Sigrimis, N. (IEEE Control systems magazine)
Modern agricultural business is becoming increasingly reliant on computer-based systems, automation, and robotics that are taking over many of the tedious tasks formerly performed by humans, with superior performance in most cases. To manage the increasing complexity of agricultural systems, increasingly sophisticated methodologies are required. This has given rise to the promising field of precision agriculture, where the goal is to improve the efficiency of operation of agricultural enterprises, as well as the duality and consistency of products, by compensating for the vagueness and uncertainty of the environment. Conversely, social demand has created pressure for respectful treatment of the environment and the well-being of humans. These objectives result in new and challenging problems, problems that can only be resolved by applying advanced information and control technologies to production management of processes and farms